Robot Ethics - Coeckelbergh, Mark (Cambridge, Massachusettes: The MIT Press, 2022)
"A concise overview of the ethical issues that are likely to emerge as robots become more social and more integrated into human life"
Keywords: Robots -- Moral and ethical aspects -- Social aspects